Study of Antimicrobial Resistance of Acinetobacter Strains Isolated From Blood Cultures - H Zandi; SH Taghipoor; S Amirpoor (Tehran University of Medical Sciences, 2007)
Background: Acinetobacter spp are associated with various nosocomial infections like as septicemia and are isolated form blood cultures in hospitalized patients. Methods: In this study, 45 Acinetobacter strains were isolated from blood samples in Yazd shahid sadoughi hospital from 21 March 2005 to 20 September 2006 and were identified by biochemical tests. Antibiotic susceptibility of the strains was tested by standard disk diffusion method. Results: In this research, 45 isolates identified as Acinetobacter and of isolated strains, 88.8% of them found sensitive to imipenem and 80% to ciprofloxacin. Also 51.5% to nalidixic Acid 24.5% to trimethoprim/sulphametoxazole, 11.1% to ceftazidim and ceftriaxone, 8.8% to cefotaxime and cefexime and also 6.6% to ceftizoxime. Conclusion: Because of increasing of drug resistance in Acinetobacter spp. Isolated from blood samples, it is necessary to perform susceptibility testing, also imipenem and ciprofloxacin recommended for drug therapy.